The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/md20080521
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Sea Cucumbers and Their Beneficial Effects on Human Health

Abstract: Sea cucumbers are considered a luxury food item and used locally in traditional medication due to their impressive nutritional profile and curative effects. Sea cucumbers contain a wide range of bioactive compounds, namely phenolics, polysaccharides, proteins (collagen and peptides), carotenoids, and saponins, demonstrating strong antioxidant and other activities. In particular, phenolic compounds, mainly phenolic acids and flavonoids, are abundant in this marine invertebrate and exhibit antioxidant activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 92 publications
(108 reference statements)
1
27
0
1
Order By: Relevance
“…In particular, they engage in plants’ defense by inhibiting herbivory, ultraviolet radiation, and pathogen attacks. In addition, they are responsible for the flavor, color, bitterness, and astringency of fruits such as persimmon [ 26 ]. Phenolic compounds in plants primarily originate from phenylalanine, and to a lesser extent, tyrosine.…”
Section: Bioactive Compounds Of Plmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they engage in plants’ defense by inhibiting herbivory, ultraviolet radiation, and pathogen attacks. In addition, they are responsible for the flavor, color, bitterness, and astringency of fruits such as persimmon [ 26 ]. Phenolic compounds in plants primarily originate from phenylalanine, and to a lesser extent, tyrosine.…”
Section: Bioactive Compounds Of Plmentioning
confidence: 99%
“…For example, p -hydroxycinnamic acid is derived from tyrosine with the assistance of tyrosine ammonia-lyase (TAL), whereas trans cinnamic acid is derived from phenylalanine, catalyzing by phenylalanine ammonia-lyase (PAL). The major phenolics present in plants are flavonoids, phenolic acids, tannins, stilbenes, lignans, and coumarin [ 26 , 27 , 28 ]. Phenolic compounds are well known as antioxidants, which demonstrate inhibitory activities against α-glucosidase and tyrosinase activities as well as LDL-cholesterol, DNA, and lipid oxidation [ 29 ].…”
Section: Bioactive Compounds Of Plmentioning
confidence: 99%
“…Under stress conditions, the human body generates reactive oxygen species (ROS), and these ROS responsible for initiating various disorders in the body such as inflammatory diseases, cancer, aging, cardiovascular diseases, brain dysfunction, and cataracts (Hossain et al, 2022a;Verma & Mishra, 2014). Antioxidants have the potential to prevent free radical formation and therefore slow down the oxidative stress in the cells and exert a protective role against ROS-mediated disorders.…”
Section: Antioxidant Activities Reported From Sea Cucumbersmentioning
confidence: 99%
“…Sea cucumbers are invertebrate marine animals which are commonly used as traditional medicine in Asian countries [ 11 ], as they contain various bioactive components, including peptides, fucoidan, triterpene glycosides, cerebrosides, fucosylated chondroitin sulfate, phenols, saponin, phospholipids and essential fatty acids [ 11 , 12 ]. Based on their impressive chemical profiles, a wide range of ascribed biological functions of sea cucumbers have been reported, such as anticancer, anti-inflammation, anti-oxidation, anti-diabetes, anti-obesity, improvement of memory and learning, and anti-aging [ 11 , 13 ]. Previous study reported the anti-neurodegenerative action of the crude ethyl acetate fraction of Holothuria scabra ( H. scabra ) in C. elegans PD model [ 14 ].…”
Section: Introductionmentioning
confidence: 99%